Intrauterine exposure to a maternal low protein diet reduces adult bone mass and alters growth plate morphology in rats. - Mehta, G; Roach, H; Langley-Evans, S; Taylor, P; Reading, I; Oreffo, R; Aihie-Sayer, A; Clarke, N; Cooper, C (2002)
Epidemiological studies suggest that poor growth during fetal life and infancy is associated with decreased bone mass in adulthood. However, theses observations have not, to date, been corroborated in animal models. To address this issue we evaluated the influence of maternal protein restriction on bone mass and growth plate morphology among the adult offspring, using a rat model. Maternal protein restriction resulted in a reduction in bone area and BMC, but not BMD, among the offspring in late adulthood. The widened epiphyseal growth plate in the protein-restricted offspring is compatible with the programming of cartilage and bone growth by maternal nutrition in early life.